Polymeric electrolytes for ambient temperature lithium batteries - Farrington, G.C. (Pennsylvania Univ., Philadelphia, PA (United States). Dept. of Materials Science and Engineering) (Lawrence Berkeley Laboratory, 1991)
A new type of highly conductive Li{sup +} polymer electrolyte, referred to as the Innovision polymer electrolyte, is completely amorphous at room temperature and has an ionic conductivity in the range of 10{sup {minus}3} S/cm. This report discusses the electrochemical characteristics (lithium oxidation and reduction), conductivity, and physical properties of Innovision electrolytes containing various dissolved salts. These electrolytes are particularly interesting since they appear to have some of the highest room-temperature lithium ion conductivities yet observed among polymer electrolytes. 13 refs. 11 figs., 2 tabs.